USM OFFERS BORDERLESS, MULTICULTURAL EDUCATION AS APEX UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 March 2016 – The status of being an APEX university as well as the stunning landscape of Universiti Sains Malaysia (USM) have attracted Li Yong, 21, from China to pursue his Bachelor’s degree in USM, Penang.